Program lima tahunan pembinaan jaringan jalan di Indonesia (Departemen Pekerjaan Umum, Direktorat Jenderal Bina Marga, 1980)
The Directorate General for Highway Construction's Five Year Development Plan for Maluku Province, 1981/1982-1985/1986.